Effect of Sex and Age on Achieving Meaningful Clinical Outcomes at 5-years after Hip Arthroscopy for Femoroacetabular Impingement: A Comparative Match-Group Analysis. Issue 7 (31st July 2020) - Beck, Edward; Drager, Justin; Nwachukwu, Benedict; Jan, Kyleen; Nho, Shane; Rasio, Jonathan
Objectives: Non-modifiable factors including age and sex have been shown to effect outcomes following hip arthroscopy in patients with femoroacetabular impingement syndrome (FAIS) at short-term follow-up. However, their effect on achieving long-term meaningful outcomes has not been evaluated. As such, the purpose of this study is to compare clinical outcomes, including achieving meaningful clinical important difference (MCID) and the patient acceptable symptomatic state (PASS) at 5-years, by age and sex. Methods: 150 patients undergoing hip arthroscopy for femoroacetabular impingement by a single fellowship trained surgeon were prospectively analyzed, with 25 patients in each of the following groups: female patients younger than 30 years of age, female patients 30 to 45 years of age, female patients older than 45 years of age, male patients younger than 30 years of age, male patients 30 to 45 years of age, and male patients older than 45 years of age. Pre and postoperative functional scores were collected including the Hip Outcome Score Activities of Daily Living Subscale (HOS-ADL), Hip Outcome Score Sport-Specific Subscale (HOS-Sport), the modified Harris hip score (mHHS), and visual analog scale (VAS) satisfaction and pain at 5-year follow-up. MCID and PASS was calculated for each functional measure and compared by gender and age category. Results: At 5-year follow-up, all groups demonstrated statistically significant improvement in the functional outcome score averages and pain (p<0.001 for all). Both within gender and within age category analysis of postoperative functional scores did not demonstrate any statistically significant differences (p>0.05).Analysis of achieving MCID and PASS demonstrated that females had a higher rate of reaching the HOS-SS and mHHS threshold for achieving MCID as compared to their male counterparts (48.3% vs 58%%; p=0.008 and 54% vs 75.4%; p=0.012, respectively). Furthermore, patients <30 years old had higher rates of reaching the HOS-ADL and mHHS for achieving PASS than the two older age groups (p>0.05 for both). Conclusions: Non-modifiable factors, including age and sex, influence the rate of achieving meaningful clinical outcomes at 5-year follow up. Female patients are more likely to reach the HOS-SS and mHHS threshold for achieving MCID, while those <30 years of age are more likely to reach the HOS-ADL and mHHS threshold for achieving PASS as compared to older patients.